2020
DOI: 10.1093/alcalc/agaa116
|View full text |Cite
|
Sign up to set email alerts
|

Non-Beverage Alcohol Consumption In Izhevsk: 15 Years Later

Abstract: Aims Non-beverage alcohol was a major cause of preventable mortality of working-age males in Izhevsk (Russia) in 2003–2004. The Russian government has since taken measures to reduce availability of non-beverage alcohol. Yet, some types of non-beverage alcohol still remain available for consumers. The aim of this study was to assess the availability and sources of non-beverage alcohol in Udmurtia. Methods A survey of adults on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Besides the discussed practical aspects that have informed the subsequent validation process, the documented accounts provide deeper insights into aspects of Russian drinking patterns that might add to the understanding of the high alcohol-attributable burden of disease in Russia and ways of responding to these harms. For instance, the analyzed materials suggest that despite the various countermeasures introduced, several types of surrogate alcohols, as well as unrecorded alcohol in general, remain available in Russian communities, which is in line with the newest evidence on this topic [28,42,43]. Furthermore, this shows that Russia's national strategy to reduce alcohol consumption and the prevalence of alcohol use disorders at the population level might not have reached surrogate consumers as the most marginalized population group and that additional efforts are needed, specifically in the area of referral mechanisms between PHC and narcology services [16,42,44,45].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Besides the discussed practical aspects that have informed the subsequent validation process, the documented accounts provide deeper insights into aspects of Russian drinking patterns that might add to the understanding of the high alcohol-attributable burden of disease in Russia and ways of responding to these harms. For instance, the analyzed materials suggest that despite the various countermeasures introduced, several types of surrogate alcohols, as well as unrecorded alcohol in general, remain available in Russian communities, which is in line with the newest evidence on this topic [28,42,43]. Furthermore, this shows that Russia's national strategy to reduce alcohol consumption and the prevalence of alcohol use disorders at the population level might not have reached surrogate consumers as the most marginalized population group and that additional efforts are needed, specifically in the area of referral mechanisms between PHC and narcology services [16,42,44,45].…”
Section: Discussionmentioning
confidence: 55%
“…For instance, the analyzed materials suggest that despite the various countermeasures introduced, several types of surrogate alcohols, as well as unrecorded alcohol in general, remain available in Russian communities, which is in line with the newest evidence on this topic [28,42,43]. Furthermore, this shows that Russia's national strategy to reduce alcohol consumption and the prevalence of alcohol use disorders at the population level might not have reached surrogate consumers as the most marginalized population group and that additional efforts are needed, specifically in the area of referral mechanisms between PHC and narcology services [16,42,44,45]. Assessing unrecorded alcohol use and specifically consumption of surrogates as drinking behavior that is strongly associated with AUDs should therefore be considered when developing SBI programmes and materials in Russia and other former Soviet Union countries with similar drinking patterns and healthcare systems [46][47][48].…”
Section: Discussionmentioning
confidence: 55%
“…It is surprising that these individuals get so little attention. Although there are a limited number of studies examining NBA consumption, similar proportions have been reported in street-entrenched individuals in Russia and Australia [ 27 , 38 ]. Within this sample, NBA consumers were older, experienced greater social and physical instability, and reported increased levels of psychological distress including symptoms of suspicion, paranoia, nervousness, worry, and frustration.…”
Section: Discussionmentioning
confidence: 77%
“…Despite it being recorded in all regions of the world, most research on unrecorded alcohol (any alcohol produced and/or consumed that is not officially registered, including NBA) comes from Russia and former parts of the Soviet Union [ 24 – 26 ]. For instance, a survey among adults in Izhevsk, Russia, reported a high prevalence of NBA consumption (28%), and sociodemographic characteristics of NBA consumers reported in the study included being single, unemployed or retired, younger than 19 or older than 29 years, having lower educational status, and having lower income [ 27 ]. In North America, previous studies have mostly comprised of semi-structured qualitative interviews with members of managed alcohol programs (MAPs) and community leaders, who have provided insight into the alcohol-related harms experienced, and have reported the impacts of various care services on alcohol consumption patterns, physical and mental health, quality of life, etc.…”
Section: Introductionmentioning
confidence: 99%
“…По расчетам ФГБУ «ЦНИИОИЗ» Минздрава России, в 2017 г. в России потребление этанола составило 9,66 литра на душу населения, при этом большая часть в структуре потребления этанола (57%) пришлась на крепкие алкогольные напитки 1 . «Северный» тип потребления алкоголя, реализуемый в России (Rehm 2006), характеризуется также распространённостью эпизодического потребления алкоголя в больших количествах (запоями); кроме того, треть от общего потребления алкоголя составляет незарегистрированное потребление, представленное в основном сверхкрепкими спиртами -самодельными напитками и суррогатами (самогон, асептолин, «боярышники») (Korotayev et al 2021). «Северный» тип потребления алкоголя является наиболее опасным.…”
Section: Introductionunclassified